Quality of life can be good after slide tracheoplasty for long-segment tracheal stenosis. (21st August 2019) - Wray, Jo; Ryde, Matthew; Butler, Colin R; Hewitt, Richard J
Abstract: OBJECTIVES: The objectives of this study were to measure 'health-related quality of life' (HRQoL) in children following slide tracheoplasty for long-segment tracheal stenosis (LSTS) and to explore the relationship of comorbidities and parental mental health with HRQoL outcomes. METHODS: A cross-sectional study was undertaken with children who had undergone slide tracheoplasty. Participants included parents and children (age 5–15 years) recruited over a 13-month period, who were asked to complete validated measures of HRQoL, development and behaviour. Scores were compared to published norms. RESULTS: Forty-two children (male 69%; n = 29) were included; mean age was 5.3 (standard deviation 3.5) years and mean follow-up was 45 (range 4–179) months. Mean total HRQoL scores for children with repaired LSTS did not differ from those of healthy norms other than for children aged 13–23 months, but 10 children (24%) had scores >2 SD below the mean for healthy children. HRQoL was poorer in children with non-cardiac congenital comorbidities than in those with isolated LSTS (mean scores 60.34 ± 17.19 and 85.52 ± 12.19, respectively, P = 0.01). There was good agreement between children's and parents' scores, although children rated their HRQoL as better than their parents did. Anxious parents rated their children's HRQoL as significantly worse than non-anxious parents ( P <0.001). CONCLUSIONS: Older children with isolated LSTS can have excellent HRQoL after surgery. Younger children, at an earlier time point postoperatively, and those with non-cardiac congenital comorbidities have poorer HRQoL. Further longitudinal evaluation is required to identify psycho-social (including parental) predictors of outcome which may inform, or be amenable to, intervention.